2002
DOI: 10.1063/1.1503352
|View full text |Cite
|
Sign up to set email alerts
|

Effective-medium theories for predicting hydrodynamic transport properties of bidisperse suspensions

Abstract: Effective-medium theories for predicting conditionally averaged velocity field and hydrodynamic transport coefficients of monodisperse suspensions are extended to bidisperse suspensions. The predictions of the theory are shown to agree very well with the results of direct numerical simulations of bidisperse suspensions with hard-sphere configurations up to volume fractions at which phase separation in bidisperse hard-sphere systems are observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…As pointed out by Dodd et al [35], the above choice of R is necessary to ensure that the conditionally averaged field has the correct behavior at large distances from the test particle for the problem of determining the averaged diffusivity of integral membrane proteins. Subsequent studies showed that the above choice also yields excellent estimates of the effective properties even when it has no rigorous basis (as e.g., see [33,39]). Random suspensions with a hardsphere potential have a non-zero S(0) even in the dilute limit, which is accurately given by the Carnahan-Starling approximation [40] as: ( )…”
Section: Figurementioning
confidence: 99%
“…As pointed out by Dodd et al [35], the above choice of R is necessary to ensure that the conditionally averaged field has the correct behavior at large distances from the test particle for the problem of determining the averaged diffusivity of integral membrane proteins. Subsequent studies showed that the above choice also yields excellent estimates of the effective properties even when it has no rigorous basis (as e.g., see [33,39]). Random suspensions with a hardsphere potential have a non-zero S(0) even in the dilute limit, which is accurately given by the Carnahan-Starling approximation [40] as: ( )…”
Section: Figurementioning
confidence: 99%
“…The effect of non-Newtonian flow and volume fraction / is included. This assumption agrees with the effective-medium theory (Koo and Sangani 2002), which uses models from force analysis to estimate conditionally averaged fields and, hence, the effective properties of dispersed particles and the carrier fluid. This assumption is extended to the simulation of the microscopic fluid region near the forming droplets, where the effect of other existing droplets is taken into account in the effective property while only the forming droplets from the aperture are included in NS equation solution.…”
Section: Introductionmentioning
confidence: 52%
“…The modification was, however, turned out to overpredict the sedimentation velocity. Although some numerical investigations have been performed on the bidisperse suspensions [13,14], a simple and accurate method which theoretically estimates the sedimentation velocity has seldom been presented.…”
Section: Introductionmentioning
confidence: 99%